Health education and community pharmacy - Kumar, N. (New Delhi : A.I.T.B.S. Publishers, India (Medical Publishers), 2009)
Health education is a high-profile topic for national government, local authorities, health authorities and educational agencies. Health education plays a crucial role in the development of a healthy, inclusive and equitable social, psychological and physical environment. It reflects current best practice, using an empowering, multi-dimensional, multi-professional approach which relates to all settings, organizations, and parts and levels of society, including schools, colleges, universities, the health services, the community and the workplace.
1. Introduction to Health Education and Community Pharmacy -- 2. Concept of Health -- 3. Health and Nutrition -- 4. Demography and Family Planning -- 5. First Aid -- 6. Environment and Health -- 7. Fundamentals of Microbiology -- 8. Communicable Diseases -- 9. Non-Communicable Diseases -- 10. Epidemiology -- Index.
Includes index.
Keywords: HEALTH EDUCATION; HEALTH COMMUNITY